A case study on the hidden curriculum of a university foreign languages preparatory school through perceptions - Sezen, Özlem (My University, 2011)
Bir Üniversite Yabancı Diller Hazırlık Okulunun Örtük Programının Algılar Yoluyla İncelenmesi Üzerine Bir Vaka Çalışması Bu tezin amacı örtük progamın, İstanbul Türkiye’de yer alan bir devlet üniversitesinin Yabancı Diller Hazırlık Okulunda var olup olmadığını saptamaktır. İkincil olarak, var olması durumunda kurumun örtük programının öğrencinin akademik başarısına etkisinin ortaya çıkarılması hedeflenmiştir. Çalışma aynı zamanda örtük progamın öğrenci algıları üzerinde olan etkisini de irdelemeyi amaçlamaktadır. Araştırma İstanbul’da bir devlet üniversitesinin Yabancı Diller Hazırlık Okulunda, rastgele seçilmiş katılımcı 8 öğrenci, 4 öğretim görevlisi ve 2 yönetici ile gerçekleştirilmiştir. Tezin amacını gerçekleştirmek için adı geçen kurumun resmi müfredat belgeleri alınarak analiz edilmiş ve böylece örtük program öğeleri saptanmaya çalışılmıştır. Buna ek olarak, örtük programla ilgili algıları ortaya çıkarmak için, rastgele seçilmiş öğrenciler, öğretim görevlileri ve yöneticiler ile ayrı ayrı görüşmeler yapılmıştır. Son olarak, öğrencilerin akademik başarılarını gösteren belgeler okul yönetiminden alınmış, öğrencilerin başarı durumlarıyla aynı öğrencilerin örtük program ile ilgili ifadelerinin arasındaki ilişki, Spearman Sıra Farkları Korelasyonu testi uygulanarak saptanmaya çalışılmıştır. Sonuçta, adı geçen devlet üniversitesinin yabancı diller hazırlık okulunda 2009-2010 öğretim yılında örtük programın var olduğu ve buna bağlı olarak, örtük program öğelerinin neler olduğu saptanmış, örtük programın öğrenci başarısına yüksek oranda etki ettiği görülmüştür. versite Yabancı Dil Hazırlık Okullarında Örtük Program, Örtük Program ve Öğrenci Algıları, Örtük Program ve Akademik Başarı.

A case study on the hidden curriculum of a university foreign languages preparatory school through perceptions The purpose of this thesis is to find out whether a hidden curriculum exists or not in the preparatory school of a state university, in İstanbul Turkey in 2009-2010 academic year. Then in the case of existence, it was aimed to reveal the effect of the hidden curriculum of the institution on the academic achievement of the students. The study also aims to examine the impact of a hidden curriculum on the perceptions of the students. The research was conducted with randomly chosen 8 participant students, 4 instructors and 2 administrators of a state university preparatory school in İstanbul. In order to achieve the purpose of the thesis, the official curriculum document of the institution was analyzed to identify the hidden curriculum elements that were likely to emerge. Secondly, the randomly chosen participant students, instructors and the administrative staff were interviewed separately in order to reveal their perceptions on the hidden curriculum. Thirdly, the document which showed the academic success of the students was obtained from the school administration and nonparametric Spearman’s Rank Correlation Test was applied to see the correlation between the hidden curriculum perceptions of the students obtained from the interview results and their academic achievement. In conclusion, it was found that the hidden curriculum existed in the foreign language education of the preparatory school of a state university in 2009-2010 academic year. Accordingly, the elements of the hidden curriculum were identified and analysed. Then, it was seen that the hidden curriculum of the institution affected the students’ academic achievement. Key Words: Hidden Curriculum in University Foreign Languages Preparatory School, Hidden Curriculum and Student Perceptions, Hidden Curriculum and Academic Achievement.
Bir üniversite yabancı diller hazırlık okulunun örtük programının algılar yoluyla incelenmesi üzerine bir vaka çalışması
Keywords: Üniversiteler ve Yüksekokullar; Yabancı Dil_Öğrenim ve Öğretim